(untitled) (Dimensión Empresarial, 2022)
This article analyzes the results of the evaluation of an instrument on institutional gender culture, using the principal components method. The structure and parameters of its validity and reliability are described, as well as the differences obtained by sex. The sample consisted of 301 public officials from Chile. The results yielded four components: working environment conditions, administrative processes, work-family reconciliation policies and labor equity, which explained 52.72 of the variance with a Cronbach’s Alpha of .947 Once these values ​​were obtained, the instrument is valid and reliable to assess institutional culture and identify gender biases. This instrument is expected to contribute with management indicators that support the consolidation of organizational strategies of equity and procedural justice.